S/Z - Barthes, Roland 1915-1980 (Paris Éditions du Seuil, 1970)
S/Z is Roland Barthes' structural analysis of "Sarrasine", the short story by Honoré de Balzac. Barthes methodically moves through the text of the story, denoting where and how different codes of meaning function. Barthes' study made a major impact on literary criticism and is historically located at the crossroads of structuralism and post-structuralism.
Includes text of Balzac's Sarrasine (p. 227-[258])
Keywords: Balzac, Honoré de -- 1799-1850; Literature; Semiotics; Crescendo; Philosophy